Subjetividade-corpo-terra-território: os impactos psicossociais e a resistência das mulheres atingidas pelo rompimento da barragem da mineração na bacia do rio Doce em Minas Gerais - Silva, Camilla Veras Pessoa da (2022)
The dam bursts that have occurred in Brazil in recent years have revealed the lack of safety of these large structures built around territories and communities. Large-scale mining generates several socio-environmental impacts that affect women in a particular way, due to gender inequality. The consequent disasters caused by mining dam bursts have resulted in compulsory displacement, destruction of communities, weakening of social ties, precarious living conditions, and systematic violations of the rights of the affected populations. The present study aimed to understand the meanings attributed to the experience of the women affected by the disaster resulting from the collapse of mining dams in the Doce River basin, in the region of MarianaMG. Through the narratives produced by the women, we aimed to identify and analyze the psychosocial impacts and resistance strategies that historically occur in their territories. To understand the subjective dimension and the psychosocial impacts, this research was based on the theoretical formulation about subjectivity and its relation to the concept of body-land-territory elaborated by the authors of Latin American community feminism. The research has a bibliographical character and used as a source of data, the reports and interviews of the affected women present in technical reports, books, audiovisual works and journalistic articles published in the media. Three open interviews were also conducted with black women from territories near the "epicenter" of the mud. The methodological procedure for apprehending reality is anchored in the materialist-historical-dialectical method adopted by Socio-Historical Psychology. The narratives were organized in nuclei of meanings that gather the set of senses and meanings broken down into units that showed that the psychosocial impacts experienced by the women refer to the loss of territory, housing and way of life, the overload of domestic work, the greater vulnerability to physical illness and psychological suffering, the exposure to domestic and gender violence and the exclusion and difficulty of access to the measures of integral reparation. Women still figure as protagonists of community mobilization and social participation spaces in favor of rights and justice in their territories, which reaffirms that in the territories where there is spoliation and capitalist extraction, women are in the front line of the fight for rights and the defense of nature